Quenching and partitioning (Q&P) processing of fully austenitic stainless steels. (July 2017) - Wendler, M.; Ullrich, C.; Hauser, M.; Krüger, L.; Volkova, O.; Weiß, A.; Mola, J.
Abstract: A novel quenching and partitioning (Q&P) processing was applied to the steel Fe-15Cr-3Ni-3Mn-0.5Si-0.12N-0.16C (wt.-%) with an almost fully austenitic microstructure in the solution annealed condition. The Q&P processing consisted of a subzero cooling step and a partitioning step at 450 °C. The fraction of α ′-martensite after the Q&P processing was nearly 58 vol%. During partitioning, M3 C precipitates with an average size of 20 nm formed inside the α ′-martensite. Concurrently, the interstitial content of austenite was increased by an average of almost 0.1 wt.-%. After Q&P processing, the stainless steel exhibited outstanding mechanical properties including a yield strength of 1050 MPa, an ultimate tensile strength of 1550 MPa, and a tensile elongation of 22% at room temperature. Reduction in the tensile test temperature from 100 °C to −40 °C facilitated the strain-induced α ′-martensite formation and led to the simultaneous enhancement of strength and ductility. The enhancement of tensile ductility in spite of the strain-induced α ′-martensite formation ( α ′-transformation-induced plasticity effect) was attributed to differences in the stability of austenite mainly caused by its non-uniform interstitial enrichment. Graphical abstract: Image